2008
DOI: 10.1002/jnr.21701
|View full text |Cite
|
Sign up to set email alerts
|

Novel expression of PINCH in the central nervous system and its potential as a biomarker for human immunodeficiency virus‐associated neurodegeneration

Abstract: Particularly interesting cysteine histidine-rich (PINCH) protein functions as a shuttling protein in Schwann cells after peripheral nerve damage, during repair and remodeling, and in maintaining neuronal polarity. However, the presence of PINCH in the human CNS during disease has not been addressed. Because HIV-associated damage to cells of the CNS involves dysregulation of neuronal signaling and white matter damage, we hypothesized that PINCH may play a role in neuropathological processes during the course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 27 publications
3
36
0
1
Order By: Relevance
“…Distinct PINCH bands were detected at approximately 55 and 71 kDa (Figure 1A), as previously reported [4, 6]. A third PINCH immunoreactive band was detected at approximately 84 kDa in some cases, reminiscent of the approximate size detected by immunoprecipitation of PINCH and hpTau [6].…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Distinct PINCH bands were detected at approximately 55 and 71 kDa (Figure 1A), as previously reported [4, 6]. A third PINCH immunoreactive band was detected at approximately 84 kDa in some cases, reminiscent of the approximate size detected by immunoprecipitation of PINCH and hpTau [6].…”
Section: Resultssupporting
confidence: 85%
“…Moreover, our data show that increased CSF levels of PINCH correspond with a more favorable immune response as defined by improved CD4 count. Previous data reported that increased PINCH is observed in the brains and CSF of HIV patients, but it was also shown that patients with HIVE had more PINCH in their brains compared to CSF [4]. Likewise, HIV patients with no CNS alterations had less PINCH in the brain and more in the CSF.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations